Aquatic Plant Diversity in Italy: Distribution, Drivers and Strategic Conservation Actions - Bolpagni, Rossano; Laini, Alex; Stanzani, Chiara; Chiarucci, Alessandro (Frontiers in Plant Science, 2018)
Italy is recognized as one of the prominent hot spot areas for plant diversity at regional and global scale, hosting a rich range of ecosystems and habitat types. This is especially true considering aquatic habitats, which represent a major portion of the total water surfaces in the Mediterranean region. Nevertheless, only a scant attention was paid to clarify the species richness of aquatic plant and its contribution to the total diversity at the country scale, despite such plants are seriously threatened at multiple scales. This paper provided the first comprehensive inventory of aquatic plants at the whole country scale, collecting data on species’ distribution, trends, and explanatory determinants of species richness. We confirmed the key contribution of Italy to the regional and global aquatic plant diversity with a total of 278 species recorded since 2005, equal to the 88.5%, 55.9% and ~10% of the richness estimated at European/Mediterranean, Palearctic and global scale, respectively. Ten species are considered extinct in the wild [among which Aldrovanda vesiculosa L., Caldesia parnassifolia (Bassi ex L.) Parl., Helosciadium repens (Jacq.) W.J.D. Koch, and Pilularia globulifera L.], four were doubt [among which Luronium natans (L.) Raf., Utricularia intermedia Hayne, and U. ochroleuca R.W. Hartman.], and nine were erroneously reported in the past, among which Isoëtes lacustris L., Myosotis rehsteineri Wartm., and Ranunculus aquatilis L. Only 18 species – mainly helophytes (14) – were present in all the 20 Italian regions, whereas hydrophytes showed most scanty regional frequencies. Temperature, latitude, area and water resources availability are the main drivers of aquatic plant spatial arrangement and diversity. Furthermore, the number of inhabitants per km2 well described the number of “lost species” since 2000. The findings of the present survey call for an urgent elaboration of large-scale strategies to ensure the survival of aquatic plants, stressing on multiple functions played by aquatic plants in supporting national economy and human well-being. In this context, Italy can play a fundamental role guaranteeing temporary refuge for projected or expected species migrations along latitude and longitude gradients. Besides, in hyper-exploited landscapes man-made water bodies can further enhance the achievement of minimum conservation targets.